Kinetics of maize cob and bean straw pyrolysis and combustion - Okot, David K.; Bilsborrow, Paul E.; Phan, Anh N.; Manning, David A.C. (Heliyon, 2023)
Kinetic studies are important for the design and optimisation of thermochemical processes. This study involved analysis of the pyrolysis and combustion behaviour of the agricultural residues (bean straw and maize cob) by non-isothermal thermogravimetric analysis. Increasing the heating rate from 10 to 40 K min -1 during both combustion and pyrolysis increased the degradation rate of both feedstocks and the gaseous yields of H2O, CO and CO2. The activation energies determined by the Flynn-Wall-Ozawa and Kissinger-Akahira-Sunose methods varied which reveals that the pyrolysis and combustion of these agricultural residues are complex processes involving multiple reactions. The average activation energy of maize cob and bean straw were 214.15 and 252.09 kJ mol -1 for pyrolysis and 202.26 and 165.64 kJ mol -1 for combustion, respectively. The order of reaction ranged between 9.0-10.3 and 6.3–13.3 for both feedstocks in combustion and inert environments, respectively. Modelled data is important to enable the optimisation of reactor design for pyrolysis and combustion for energy generation from agricultural residues.
Keywords: Maize cob; Bean straw; Kinetic study; Activation energy; Pyrolysis and combustion